Prevalence of Cardiovascular Risk Factors and Complications in Adolescents - Aston T., Fairweather K., Gainsborough V. (Open Journal of Physicians and Surgeons, 2025)
Early identification of risk factors for cardiovascular diseases in patients with arterial hypertension, especially with metabolic disorders, allows for the most objective assessment of the risk of complications, and therefore, to slow down the appearance of severe complications. Objective: to study the prevalence of cardiovascular disease risk factors in hypertensive patients with metabolic disorders. According to the cardiovascular risk stratification, all patients selected for the study were characterized by a very high risk of developing cardiovascular complications. The patients underwent a general clinical examination and a questionnaire to identify risk factors. Studies have shown that most patients had a significant number of factors that negatively affect the prognosis of hypertensive disease. Frequent psychoemotional stress was found in 76% of patients, overweight in 64% of patients. Physical inactivity occurred in 50% of patients. A burdened heredity of cardiovascular diseases (stroke, myocardial infarction or hypertension in close relatives) was in 45% of study participants. Smoking, as a risk factor, was noted in 22% of patients, alcohol abuse - in 10% of patients. Hypercholesterolemia was registered in 73% of patients. When calculating the body mass index among the examined patients, it was found that only 5% of patients had normal arterial hypertension. Obesity is noted in 30% of cases; obesity of the 1st degree - in 38% of patients; obesity of the 2nd degree - in 23% of cases; obesity of the 3rd degree - in 4% of patients. Conclusions. The study showed that in patients with arterial hypertension with metabolic disorders, the most common risk factors are: burdened heredity for cardiovascular diseases, psycho-emotional stress, hypercholesterolemia, excess body weight. Identification of risk factors must be taken into account when planning individual preventive measures, the main goal of which is to prevent the development of complications and improve the quality of life.